Marine wildlife in Brazilian zoohandicrafts: assessing the expansion of an uncontrolled trade - Ruenes, Greicy F.; Zalmon, Ilana Rosental; Novelli, Ronaldo; Vidal, Marcelo D.; Siciliano, Salvatore (Frontiers in Marine Science, 2023)
The trade of wild animal parts as souvenirs, hereafter termed zoohandicrafts, has witnessed significant growth in Brazil due to increasing tourism and the associated demand for souvenirs. This study aimed to investigate the diversity of marine wildlife traded as zoohandicrafts along the Brazilian coast, identify the prevalent categories for these products, and assess the extent of this trade across the country. Sampling was conducted in 23 markets at tourist destinations, covering 11 states from the Northern, Northeastern, Southeastern, and Southern regions of Brazil, between 2017 and 2022. A total of 160 items or voucher specimens were examined, revealing the presence of 68 invertebrate species and two fishes. Statistical analysis indicated significant variations in the number of species across different categories of use and within the visited states and regions. Several species were found to serve multiple purposes. Whole mollusk shells constituted the most frequently traded item, with 58 identified species. Non-metric multidimensional scaling (NMDS) revealed two distinct groups—one including species with diverse uses in all regions of Brazil and the other encompassing species predominantly associated with decoration and religious purposes—particularly in the Northeastern and Southeastern regions of Brazil. An increasing diversity of species and a lower frequency of use were observed in the Southeastern region, relative to the Northeastern region. Approximately 20% of the species recorded are exclusively from the Indo-Pacific Ocean and are regarded as non-native to Brazil. Only 12 of the species were listed in the International Union for the Conservation of Nature (IUCN) Red List, and two are regulated by the Convention on International Trade in Endangered Species (CITES). This research sheds light on the status of the zoohandicraft trade in Brazil and highlights the lack of regulatory measures, the potential threats posed to biodiversity loss, and the economic importance of these species for people’s livelihoods. Further investigations are required to gain a comprehensive understanding of the actual social, economic, and ecological impacts of the trade in zoohandicrafts in Brazil and to devise strategies that promote both conservation and the socioeconomic wellbeing of all people involved in this commerce, from sourcing, production, distribution, and sale.